1998
DOI: 10.1021/ie9709345
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Water Oxidation of NH3 over a MnO2/CeO2 Catalyst

Abstract: Catalytic oxidation of ammonia in supercritical water (SCW) was studied using a continuous-flow, packed-bed reactor at temperatures ranging from 410 to 470 °C, a nominal pressure of 27.6 MPa, and reactor residence times of less than 1 s. The kinetics and catalyst performance of MnO2/CeO2 for oxidation of ammonia in SCW was evaluated. In this reaction environment, ammonia was predominantly converted into molecular nitrogen (N2), and the rate of ammonia conversion was enhanced by MnO2/CeO2. For example, 40% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(99 citation statements)
references
References 32 publications
1
92
1
2
Order By: Relevance
“…It was suggested that the synergistic mechanism could be explained by considering the effective activation of lattice oxygen species over the surface of the Ce/OMS-2 catalyst [40,41]. The promoting effect of Ce in the Ce/OMS-2 catalysts could be proposed by the following chain reactions similar to Ding et al [42].…”
Section: Promoting Effect Of Ce In the Ce/oms-2 Catalystmentioning
confidence: 99%
“…It was suggested that the synergistic mechanism could be explained by considering the effective activation of lattice oxygen species over the surface of the Ce/OMS-2 catalyst [40,41]. The promoting effect of Ce in the Ce/OMS-2 catalysts could be proposed by the following chain reactions similar to Ding et al [42].…”
Section: Promoting Effect Of Ce In the Ce/oms-2 Catalystmentioning
confidence: 99%
“…For example, ammonia and methanol are relatively stable compounds in the supercritical water and require high temperatures, longer residence times or catalysts for better gasification. Supercritical water oxidation has been shown to be an effective technology for destroying such molecules and promotes faster reaction rates, rapid and complete oxidation [22,23].…”
Section: Supercritical Water Oxidationmentioning
confidence: 99%
“…There has been considerable work with reactor alloys in an attempt to control and promote these catalytic effects (Afif et al, 2011). The fabrication of a fixed-bed catalyst from the same Inconel material used in the reactor, for example, increased gasification efficiency four-fold (Ding et al, 1998).…”
Section: Corrosion Influence On Reactor Designmentioning
confidence: 99%